2021
DOI: 10.3390/molecules26226793
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Dehydrogenase Functions in Glutamic Acid Metabolism and Stress Resistance in Pyropia haitanensis

Abstract: Pyropia haitanensis is an important laver species in China. Its quality traits are closely related to the content of glutamic acid. Glutamate dehydrogenase (GDH) is a crucial enzyme in the glutamic acid metabolism. In this study, two GDH genes from P. haitanensis, PhGDH1 and PhGDH2, were cloned and successfully expressed in Escherichia coli. The in vitro enzyme activity assay demonstrated that the catalytic activity of PhGDHs is mainly in the direction of ammonium assimilation. The measured Km values of PhGDH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The current results are consistent with previous research findings, in which the amino acid content of tempeh increased significantly during aerobic fermentation but increased insignificantly during anaerobic fermentation ( P < 0.05) ( 52 ). Glutamate can be synthesized using 2-oxoglutarate catalyzed by glutamate dehydrogenase (GLDH) ( 53 ). In the present study, AS had significantly higher levels of proline and N-acetylglutamic acid than NS.…”
Section: Resultsmentioning
confidence: 99%
“…The current results are consistent with previous research findings, in which the amino acid content of tempeh increased significantly during aerobic fermentation but increased insignificantly during anaerobic fermentation ( P < 0.05) ( 52 ). Glutamate can be synthesized using 2-oxoglutarate catalyzed by glutamate dehydrogenase (GLDH) ( 53 ). In the present study, AS had significantly higher levels of proline and N-acetylglutamic acid than NS.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, about 10.75% (331 out of 3078 genes) LOF showed moderate to high expression. Some specific examples of these genes with known functions include: (i) a mitochondrial enzyme known as glutamate dehydrogenase (Phatr3 J13951), which has been reported to play a crucial role in carbon and nitrogen metabolism as well as energy supply under abiotic stresses in Arabidopsis and the red alga Pyropia haitanensis [71][72][73][74] ; (ii) an LCH15 protein (Phatr3 J48882), which functions as a chlorophyll binding protein and potentially contributes to the adaptation to different light conditions in laboratory cultures and (iii) a heat shock transcription factor (Phatr3 J49594) which similarly may contribute to the adaptation to lab culture temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the metabolic engineering of glutamate dehydrogenase (GDH) genes from Pyropia haitanensis , a type of red algae species, may provide insights on GDH enzyme activity and its glutamic acid metabolism, which contributes to its nutritional value and flavor. Herein, Li et al have shown that PhGDH1 and PhGDH2 , two GDH genes from P. haitanensis , have differential K m values towards various substrates, such as NADH, (NH 4 ) 2 SO 4 , and α-oxoglutarate [ 11 ]. It was shown that both enzymes have higher affinity for NH 4 + , suggesting that their capacity for assimilating ammonium is more effective than that of other, higher plants.…”
Section: Applications Of Biomolecules In the Agricultural And Food Pr...mentioning
confidence: 99%